The Legality of Stablecoins as Digital Financial Instruments in Sharia Economic Law - Ariyadi; Parman Komarudin; Syaikhu; Arisman; Muhammad Rifqi Hidayat (Jurnal Hadratul Madaniyah, 2026)
The development of financial technology has given rise to various digital payment instruments, one of which is stablecoin. Stablecoins exist as digital assets designed to maintain stable value through support from certain assets such as fiat currency, gold, or algorithms. The presence of stablecoins has sparked legal debate, particularly from the perspective of Islamic Economic Law, as on one hand they offer digital transaction efficiency, yet on the other hand they may contain elements of gharar, riba, and speculation. This study aims to analyse the legality of stablecoins as digital payment instruments from the perspective of Islamic Economic Law, focusing on the elements of gharar, riba, and value stability. The study uses a normative juridical method with a conceptual approach, a legislative approach, and a maqashid sharia approach. The data sources were obtained from the Qur’an, Hadith, DSN-MUI fatwas, Bank Indonesia and OJK regulations, as well as scientific literature related to digital assets and Islamic finance. The research findings indicate that stablecoins have the potential to be accepted within the Islamic economic system if they meet the principles of transparency, possess clear underlying assets, avoid excessive speculation, and maintain transaction value stability. However, algorithmic stablecoins may carry high gharar due to unclear asset backing and system volatility. From the perspective of maqashid syariah, stablecoins can support the benefits of the digital economy if strictly regulated through Sharia regulations and state supervision. This research emphasises the importance of formulating specific Sharia regulations regarding stablecoins within Indonesia's digital financial system.